Asymmetric 1, 4‐Addition Reactions Catalyzed by N‐Terminal Thiourea‐Modified Helical l‐Leu Peptide with Cyclic Amino Acids. Issue 43 (17th June 2021) - Sato, Kazuki; Umeno, Tomohiro; Ueda, Atsushi; Kato, Takuma; Doi, Mitsunobu; Tanaka, Masakazu
Abstract: N‐terminal thiourea‐modified l ‐Leu‐based peptide (3, 5‐diCF3 Ph)NHC(=S)‐(l ‐Leu‐l ‐Leu‐Ac5 c)2 ‐OMe with five‐membered ring α, α‐disubstituted α‐amino acids (Ac5 c) catalyzed a highly enantioselective 1, 4‐addition reaction between β‐nitrostyrene and dimethyl malonate. The enantioselective reaction required only 0.5 mol % chiral peptide‐catalyst in the presence of i Pr2 EtN (2.5 equiv.), and gave a 1, 4‐adduct with 93 % ee of an 85 % yield. As Michael acceptors, various β‐nitrostyrene derivatives such as methyl, p ‐fluoro, p ‐bromo, and p ‐methoxy substituents on the phenyl group, 2‐furyl, 2‐thiophenyl, and naphthyl β‐nitroethylenes could be applied. Furthermore, various alkyl malonates and cyclic β‐keto‐esters could be used as Michael donors. It became clear that the length of the peptide chain, a right‐handed helical structure, amide N−Hs, and the N‐terminal thiourea moiety play crucial roles in asymmetric induction. Abstract : N‐terminal thiourea‐modified helical l ‐Leu‐based peptide (0.5 mol %) catalyzed a highly enantioselective 1, 4‐addition reaction between various β‐nitrostyrenes and dialkyl malonates to give 1, 4‐adducts with a 65–96 % ee. The length of the peptide chain, right‐handed helical structure, amide N−Hs, and the N‐terminal thiourea moiety played crucial roles in the asymmetric induction.